How air pollution influences the difference between overweight and obesity: a comprehensive analysis of direct and indirect correlations - Yu, Muchun; Xie, Jinchen; Liu, Yanyan (Frontiers in Public Health, 2024)
Background Obesity, characterized by excessive or abnormal fat accumulation, is a major public health concern. Air pollution is a significant potential obesogenic factor, but the clear direct and indirect correlations between air pollution and obesity remain unclear. This study aims to provide a comprehensive understanding of the relationship between air pollution and obesity by identifying both direct and indirect causal correlations. Methods We used nationally representative data from the China Family Panel Survey. Air pollution concentrations were quantified as the mass (μg) of air pollutants per cubic meter (m3) based on nationally representative statistical data. To minimize statistical bias inherent in traditional methods, the direct relationship between air pollution and obesity was estimated using a regression discontinuity model, while the potential underlying mechanisms were explored through structural equation modeling. Results Air pollution was generally positively associated with overweight/obesity (OROWAQI = 1.109, [95%CI = 1.027:1.305], OROBAQI = 1.032, [95%CI = 1.006:1.217], ORSOAQI = 1.069, [95%CI = 1.014:1.208], PM2.5 and PM10 positively affected overweight/obesity (OROWPM2.5 = 1.173, [95%CI = 1.094:1.252], OROBPM2.5 = 1.022, [95%CI = 1.016:1.028], ORSOPM2.5 = 1.035 [95%CI = 1.015:1.055], OROWPM10 = 1.053, [95%CI = 1.030:1.076], OROBPM10 = 1.008 [95%CI = 1.006:1.010], ORSOPM10 = 1.013 [95%CI = 1.007:1.019]), and SO2 and CO posed negative impacts on overweight/obesity (OROWSO2 = 0.972, [95%CI = 0.965:0.979], OROBSO2 = 0.997, [95%CI = 0.996:0.998], ORSOSO2 = 0.994, [95%CI = 0.991:0.997], OROWCO = 0.986, [95%CI = 0.980:0.992], OROBCO = 0.998, [95%CI = 0.997:0.999], ORSOCO = 0.999, [95%CI = 0.998:0.999]). The impact of air pollution on overweight/obesity was more significant among men, older individuals, and rural populations compared to women, younger individuals, and urban populations. Furthermore, the relationship between air pollution and overweight/obesity was mediated by social behavior determinants, including physical activity (β = 0.18, [95%CI = 0.04:0.29]), sedentary behavior (β = 0.12, [95%CI = 0.04:0.16]), sleep (β = 0.06, [95%CI = 0.02:0.13], smoking (β = 0.07, [95%CI = 0.02:0.15]), alcohol consumption (β = 0.08, [95%CI = 0.04:0.11]), and mental health (β = 0.06, [95%CI = 0.01:0.09]). Conclusion Air pollution was generally associated with an increased risk of overweight and obesity, with PM2.5 and PM10 having a positive influence, while SO2 and CO had a negative impact. The effect of air pollution was more pronounced among men, older individuals, and rural populations compared to women, younger individuals, and urban populations. Additionally, social behavior factors, such as physical activity, sedentary behavior, sleep, smoking, alcohol consumption, and mental health, predominantly mediated the relationship between air pollution and obesity.